Tables for the Design Strength of Eccentrically-Loaded Single Angle Struts - Sakla, Sherief S.S. (Engineering Journal, 2001)
The design of eccentrically-loaded single angle struts is a tedious and lengthy procedure. A computer program was developed to perform these time consuming calculations and generate design tables for 36 ksi and 50 ksi equal and unequal leg angles. The program uses the less conservative approach permitted by the AISC Specification for Load and Resistance Factor Design of Single-Angle Members (AISC, 1993). This approach involves applying the interaction equation separately at the corner and the two leg tips of the angle, with the proper signs for compression and tension. Two step-by-step numerical examples are presented in this paper to outline the procedure implemented to generate load tables for equal and unequal leg angles.